Social representations of climate change between urban and rural population in Chile - Peña-Garay, Matías; Sandoval Díaz, José Sebastián (Revista de Psicología, 2024)
Chile is a country vulnerable to climate change, presenting significant challenges for its psychosocial approach. Despite recent advances in psychological research on this phenomenon, there is a gap in understanding how the model of social representations of climate change varies between urban and rural areas in Chile. Methodologically, a mixed research design was implemented, gathering data through an online questionnaire that was administered to 238 participants from the central-southern region of Chile. This questionnaire was based on the structural approach of the theory of social representations, using a prototypical and categorical analysis. The results indicate that, although there are common representations in both populations regarding the negative view of the consequences of climate change and the relevance of its anthropogenic causes, the meanings about the effects and consequences of this differ markedly, thus influencing how environmental problems and solutions are prioritized in each context. In conclusion, this study provides evidence on how representations of climate change and its potential solutions vary territorially between urban and rural contexts. Additionally, it highlights the usefulness of the social representations model for investigating this issue from a psychosocial perspective.